PELATIHAN PEMANFAATAN TEKNOLOGI TEPAT GUNA ALAT DESTILASI BAGI KELOMPOK TANI TANAMAN NILAM DESA PASENAN KECAMATAN STL ULU TERAWAS KABUPATEN MUSI RAWAS - Tri Ariani; Wahyu Arini; Endang Lovisia; Ovilia Putri Utami Gumay (LP4MK STKIP PGRI Lubuklinggau, 2023)
This program aims to help the people of Pasenan Village to be able to make a simple distillation device, which is used by residents to convert patchouli plants into essential oils. Most of the residents of Pasenan have gardens planted with patchouli plants, but local residents have not done the conversion of patchouli plants into essential oil. The limited knowledge of the community about the patchouli distillation process is one of the obstacles faced by the community. Patchouli plants are only dried and sold directly to collectors. The condition of the people of Pasenan Village, STL Ulu Terawas Subdistrict, most of whom do not know the selling value of patchouli if it is processed into essential oil, so it is necessary to update information on science and technology, namely by holding socialization and training on the use of patchouli distillation tools into essential oils. The implementation stages in this PKM are the preparation stage, the training/socialization stage, the design and manufacture stage of the distillation apparatus, the implementation stage, and the evaluation stage. The target in this training is patchouli farmers in Pasenan village. The instrument used in this PKM is a knowledge and skills questionnaire. From the analysis of the results of the knowledge questionnaire, the average value of knowledge was 86, 7 in the